An experimental and analytical study of micro-laser line thermography on micro-sized flaws in stitched carbon fiber reinforced polymer composites. (1st April 2016) - Zhang, Hai; Yu, Lingyao; Hassler, Ulf; Fernandes, Henrique; Genest, Marc; Robitaille, François; Joncas, Simon; Holub, Wolfgang; Sheng, Yunlong; Maldague, Xavier
Abstract: Stitching is used to reduce incomplete infusion of T-joint core (dry-core) and reinforce T-joint structure. However, it might cause new types of flaws, especially micro-sized flaws. In this paper, a new micro-laser line thermography (micro-LLT) is presented. X-ray micro-computed tomography (micro-CT) was used to validate the infrared results. The micro-LLT and micro-CT inspection are compared. Then, a finite element analysis (FEA) is performed. The geometrical model needed for finite element discretization was developed from micro-CT measurements. The model is validated for the experimental results. Finally a comparison of the experiments and simulation is conducted. The infrared experimental phenomenon and results are explained based on the FEA results.